An updated review summarizing the anticancer potential of flavonoids via targeting NF-kB pathway - Pandey, Pratibha; Lakhanpal, Sorabh; Mahmood, Danish; Kang, Han Na; Kim, Byunggyu; Kang, Sojin; Choi, Jinwon; Choi, Min; Pandey, Shivam; Bhat, Mahakshit; Sharma, Shilpa; Khan, Fahad; et al. (Frontiers in Pharmacology, 2025)
Nuclear factor-κB (NF-κB) cell signaling pathway is essential for the progression and development of numerous human disorders, including cancer. NF-κB signaling pathway regulates a wide range of physiological processes, such as cell survival, growth, and migration. Deregulated NF-kB signaling resulted in unregulated cell proliferation, viability, movement, and invasion, thus promoting tumor development. Recent findings have increasingly shown that plant derived phytochemicals that inhibit NF-κB signaling have the potential to be employed in cancer therapeutics. Flavonoids are a group of polyphenolic natural compounds present in various plants and their fruits, vegetables, and leaves. These compounds have numerous medicinal properties owing to their antioxidant, anti-inflammatory, antiviral, and antitumor characteristics. The main mechanism by which these flavonoids exhibit their anticancer potential is via potent antioxidative and immunomodulatory actions. Current research reports have demonstrated that these flavonoids exhibited their anticancer effects via suppressing the NF-κB signaling. Based on these facts, we have comprehensively outlined the cancer promoting role of NF-κB pathway in various processes including tumor progression, drug resistance, angiogenesis and metastasis. In addition to these, we also summarize the anticancer potential of flavonoids by specifically targeting the NF-κB pathway in various types of cancers.